Rationale for the Application of Wells with a Wave-Shaped Horizontal Termination for the Conditions of the Srednebotuobinskoye Field - Z. Kolev; E. Mamchistova; A. Skarednov; S. Gracheva; T. Rogozina (Наука. Инновации. Технологии)
Introduction. Currently, most of the developed oil deposits are classified as complex fields. The specificity and main difficulties in the development of such deposits are determined by the conditions of occurrence in the productive horizon, which differ sharply in the formation anisotropy, as well as the presence of underlying formation water. The issue of operating wells of complex geometry is especially acute. As a model, a mathematical model developed by the authors is proposed, which makes it possible to describe the inflow to a production well of complex geometry. The results obtained when applying the author’s model and comparing the data with the known formulas for the inflow to a horizontal well showed good convergence. The proposed single-phase inflow model makes it possible to predict the potential flow rate of an undulating well during the development of the Srednebotuobinskoye field.Materials and methods of research. The paper considers a mathematical model developed by the authors, which makes it possible to describe the inflow to a production well of complex geometry. The results obtained when applying the author’s model and comparing the data with the known formulas for the inflow to a horizontal well showed good convergence. The dependence of well productivity with a wavy trajectory on the anisotropy and the number of sinusoid cycles is shown. The area of application of wells with an undulating trajectory and the application of the proposed single-phase filtration model for predicting the productivity of a undulating well that has penetrated the oil rim of the Botuobinsky horizon with a gas cap and bottom water are determined.Results and Discussion. The joint solution of the equation for the distribution of reservoir pressure and pressure in the wellbore makes it possible to obtain a system of equations, the solution of which is the flow rates of the well segments. A horizontal well can be considered as a special form of undulating well as the undulation index is zero. The paper proposes a numerical-analytical model for predicting and evaluating the productivity of undulating wells. The results obtained when applying the author’s model and comparing the data with the known formulas for the inflow to a horizontal well showed good convergence. The dependence of well productivity with a wavy trajectory on the anisotropy and the number of sinusoid cycles is shown. A numerical-analytical model is also proposed for predicting and evaluating the productivity of undulating wells.